Monitoring of population shifts in an enriched nitrifying system under gradually increased cadmium loading - ÇALLI, BARIŞ; MERTOĞLU, BÜLENT; SEMERCİ, NESLİHAN (ELSEVIER SCIENCE BV, 2008)
The changes in nitrifying bacterial population under cadmium loading were monitored and evaluated in a laboratory scale continuous-flow enriched nitrification system. For this purpose, the following molecular microbiological methods were used: slot-blot hybridization, denaturing gradient gel electrophoresis (DGGE), real-time PCR followed by melting curve analysis, cloning and sequence analysis. The initial cadmium concentration was incrementally increased from 1 to 10mg/l which led to a drop in ammonia removal efficiency from 99 to 10%. inhibition was recovered when cadmium loading was stopped. During the second application of cadmium. nitrifying population became more tolerant. Even at 15 mg/l Cd, only a minor inhibition was observed. To investigate the variations in ammonia and nitrite oxidizing bacteria populations in a period of 483 days, ammonia monooxygenase (amoA) and 16S rRNA genes-based molecular techniques were used. An obvious shift was experienced in the diversity of ammonia oxidizers after the first application of 10mg/l Cd. Metal-tolerant ammonia oxidizing species became dominant and the microbial diversity sharply shifted from Nitrosomonas and Nitrosococcus sp. to Nitrosospira sp. which were observed to tolerate higher cadmium loadings. This result indicated that the extent of nitrification inhibition was not only related to the metal concentration and quantity of microorganisms but also depended on the type of species. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Cadmium; Nitrification; amoA; DGGE; Real-time PCR; AMMONIA-OXIDIZING BACTERIA; ACTIVATED-SLUDGE PROCESS; HEAVY-METALS; NITRIFICATION INHIBITION; WASTE-WATER; REMOVAL; COPPER; NITROSOMONAS; DIVERSITY; COMMUNITIES